18F-FDG Uptake on PET/CT in Symptomatic versus Asymptomatic Carotid Disease: a Meta-Analysis. (August 2018) - Chowdhury, Mohammed M.; Tarkin, Jason M.; Evans, Nicholas R.; Le, Elizabeth; Warburton, Elizabeth A.; Hayes, Paul D.; Rudd, James H.F.; Coughlin, Patrick A.
Abstract : Introduction: The role of positron emission tomography (PET)/computed tomography (CT) in the determination of inflammation in arterial disease is not well defined. This can provide information about arterial wall inflammation in atherosclerotic disease, and may give insight into plaque stability. The aim of this review was to perform a meta-analysis of PET/CT with 18 F-FDG (fluorodeoxyglucose) uptake in symptomatic and asymptomatic carotid artery disease. Methods: This was a systematic review, following PRISMA guidelines, which interrogated the MEDLINE database from January 2001 to May 2017. The search combined the terms, "inflammation", "FDG", and "stroke". The search criteria included all types of studies, with a primary outcome of the degree of arterial vascular inflammation determined by 18 F-FDG uptake. Analysis involved an inverse weighted variance estimate of pooled data, using a random effects model. Results: A total of 14 articles (539 patients) were included in the meta-analysis. Comparing carotid artery 18 F-FDG uptake in symptomatic versus asymptomatic disease yielded a standard mean difference of 0.94 (95% CI 0.58–1.130; p < .0001; I 2 = 65%). Conclusions: PET/CT using 18 F-FDG can demonstrate carotid plaque inflammation, and is a marker of symptomatic disease. Further studies are required to understand the clinical implication of PET/CT as a risk prediction tool.